The Role of Social Media Platforms in Boosting Business Performance - Hong, Tan Lay; Huei, Lok Yee; Mathur, Garima; Jayaraman, Moganasunthari; Qixing, Mai; Aalam, Maziah Fazlin Binti Zainul; Huiqi, Mu (Advances in Global Economics and Business Journal, 2025)
This study examines how businesses utilize social media platforms to enhance business performance through social media influence, buying behavior, trust and loyalty, and overall social media usage. Using a quantitative approach, data were collected from 155 respondents across various industries and analyzed using descriptive statistics, correlation, and regression analysis. The results show high reliability, with Cronbach’s alpha values ranging from 0.827 to 0.891. Social media influence exhibits a strong positive relationship with buying behavior (r = 0.784) and trust and loyalty (r = 0.802), and emerges as the strongest predictor of business performance (β = 0.36), followed by trust and loyalty (β = 0.28) and social media usage (β = 0.15). Additionally, 93% of respondents reported purchasing products after exposure to social media content, while 92% expressed willingness to recommend businesses based on their social media presence. These findings confirm that social media functions as a strategic driver of sustainable business performance rather than merely a marketing tool.